House ownership in Selangor: A qualitative study on consumers preferences and challenges / Nur Syafiqah Packeer Mohamed - Nur Syafiqah , Packeer Mohamed (2020)
The residential real estate market in Selangor offers diverse house types following the fact that the state has highest number of workers. It is important for a proper decision-making process by taking consider a few factors such as financial and neighbourhood factors in a house purchase. Based on residential housing market data in Selangor, Petaling district was found to have the most purchases and the 2 to 2 and a half storey house type is the most purchased out of the variety, and there are also cases where there are completed houses that were not purchased by the residents, even in the lower price category. These data has been used as a base in forming the objective of the study which is to describe the factors that residents used in their decision-making model taken from consumer behaviour theory for house purchases based on location and type, and to determine the presence of challenges in preferred first house purchase along with the factors affecting it in Selangor. For this, qualitative analysis was done using phenomenological method by interviewing about 6 house owners in Selangor who were chosen using purposive and snowball sampling.